Childhood residential mobility and health in late adolescence and adulthood: findings from the West of Scotland Twenty-07 Study. Issue 10 (6th February 2012) - Brown, D; Benzeval, M; Gayle, V; Macintyre, S; O'Reilly, D; Leyland, A H
Abstract : Background: The relationship between childhood residential mobility and health in the UK is not well established; however, research elsewhere suggests that frequent childhood moves may be associated with poorer health outcomes and behaviours. The aim of this paper was to compare people in the West of Scotland who were residentially stable in childhood with those who had moved in terms of a range of health measures. Methods: A total of 850 respondents, followed-up for a period of 20 years, were included in this analysis. Childhood residential mobility was derived from the number of addresses lived at between birth and age 18. Multilevel regression was used to investigate the relationship between childhood residential mobility and health in late adolescence (age 18) and adulthood (age 36), accounting for socio-demographic characteristics and frequency of school moves. The authors examined physical health measures, overall health, psychological distress and health behaviours. Results: Twenty per cent of respondents remained stable during childhood, 59% moved one to two times and 21% moved at least three times. For most health measures (except physical health), there was an increased risk of poor health that remained elevated for frequent movers after adjustment for socio-demographic characteristics and school moves (but was only significant for illegal drug use). Conclusions: Risk of poor health was elevated in adolescence and adulthood with increased residential mobility in childhood, after adjusting for socio-demographic characteristics and school moves. This was true for overall health, psychological distress and health behaviours, but physical health measures were not associated with childhood mobility.